Development and validation of an analytical method by HPLC-DAD for determination of caffeine in products based on guarana extracts (Paullinia cupana) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Guarana (Paullinia cupana) is a native plant from the Amazon whose seeds contain a high concentration of caffeine. Aqueous extract of guarana is widely used in the world. In this study, the objective was to develop and validate a High-Performance Liquid Chromatography method for the determination of caffeine in extracts and commercial beverages based on guarana. A sensitive, simple, and viable high performance liquid chromatographic method without the need of an analyte extraction procedure was developed and validated according to Brazilian and international requirements. The method presented high performance, fulfilling Brazilian and international requirements, in addition to allowing product compliance tests. Results confirmed high selectivity and linearity (>0.999) between 5 to 135 ug/mL, with no significant matrix effect. Detection and quantification limits were 0.02 µg/mL and 2 µg/mL, respectively. Precision was less than 4 %, and accuracy varied from 99.9-120 %. Applicability of the method was demonstrated by conducting a limited evaluation in products containing caffeine. Commercial extracts showed quite different caffeine levels, while carbonated drinks follow Brazilian and American recommendations. Our results indicate that the developed method can be used to evaluate the quality of the guarana extract and of products containing caffeine.